Quorum sensing controls expression of the type III secretion gene transcription and protein secretion in enterohemorrhagic and enteropathogenic Escherichia coli - Sperandio, Vanessa (The National Academy of Sciences, 1999)
Enterohemorrhagic Escherichia coli O157:H7 and enteropathogenic E. coli cause a characteristic histopathology in intestinal cells known as attaching and effacing. The attaching and effacing lesion is encoded by the Locus of Enterocyte Effacement (LEE) pathogenicity island, which encodes a type III secretion system, the intimin intestinal colonization factor, and the translocated intimin receptor protein that is translocated from the bacterium to the host epithelial cells. Using lacZ reporter gene fusions, we show that expression of the LEE operons encoding the type III secretion system, translocated intimin receptor, and intimin is regulated by quorum sensing in both enterohemorrhagic E. coli and enteropathogenic E. coli. The luxS gene recently shown to be responsible for production of autoinducer in the Vibrio harveyi and E. coli quorum-sensing systems is responsible for regulation of the LEE operons, as shown by the mutation and complementation of the luxS gene. Regulation of intestinal colonization factors by quorum sensing could play an important role in the pathogenesis of disease caused by these organisms. These results suggest that intestinal colonization by E. coli O157:H7, which has an unusually low infectious dose, could be induced by quorum sensing of signals produced by nonpathogenic E. coli of the normal intestinal flora.